2008
DOI: 10.1210/jc.2007-2521
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Obstetrical Complications in Women withLMNA-Related Familial Partial Lipodystrophy

Abstract: In these LMNA-linked lipodystrophic patients, the prevalence of PCOS, infertility, and gestational diabetes was higher than in the general population. Moreover, the prevalence of gestational diabetes and miscarriages was higher in lipodystrophic LMNA-mutated women than previously reported in PCOS women with similar body mass index. Women with lipodystrophies due to LMNA mutations are at high risk of infertility, gestational diabetes, and obstetrical complications and require reinforced gynecological and obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 40 publications
3
60
1
2
Order By: Relevance
“…All the mentioned abnormalities are consistent with observations in FPLD patients in accordance with previous reports from literature [20,21]. On the other hand, none of the patients was overweight, while most of the patients carrying the W482R mutation described to date have had BMI above the normal range [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…All the mentioned abnormalities are consistent with observations in FPLD patients in accordance with previous reports from literature [20,21]. On the other hand, none of the patients was overweight, while most of the patients carrying the W482R mutation described to date have had BMI above the normal range [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…Vantyghem [8] demonstrated that LMNA-mutated lipodystrophic women: prevalence of PCOS was more than 50%, infertility close to 30%, miscarriages reached 50%, gestational diabetes at least 30%, and preeclampsia and fetal death above 10%. These were all higher than those found in the general population.…”
Section: Resultsmentioning
confidence: 99%
“…There are few reports in the literature describing the association of PCOS with FPLD2 [12][13][14][15].…”
Section: Pcos Secondary To Fpld2mentioning
confidence: 99%